Application of solid-phase extraction based on magnetic nanoparticle adsorbents for the analysis of selected persistent organic pollutants in environmental water: A review of recent advances. Issue 1 (2nd January 2021) - Wu, Aiming; Zhao, Xiaoli; Wang, Junyu; Tang, Zhi; Zhao, Tianhui; Niu, Lin; Yu, Wenqiang; Yang, Chunyan; Fang, Mengyuan; Lv, Hongzhou; Liu, Shasha; Wu, Fengchang
Abstract: Sample preconcentration is a critical step in the analysis of trace organic pollutants in environmental water. In recent years, solid-phase extraction based on functionalized magnetic nanoparticle (MNP) adsorbents has attracted wide attention because of its advantages in time, reagent, and labor savings, as well as its high extraction efficiency. To improve the selectivity, dispersibility, stability, and reusability of MNP adsorbents, various functional materials have been applied, including inorganic materials, carbonaceous materials, organic compounds, metal–organic frameworks, and bio-sorbents and their hybrid forms. Here, the application of solid-phase extraction based on MNP adsorbents for trace persistent organic pollutant (POP) detection in environment water from 2015 to 2019 is reviewed. In addition, the synthetic routes, characteristics of modification materials, selective sorption mechanisms, and analytical performance of these adsorbents are also discussed. The properties of environmental water samples have complicated effects on the extraction efficiency of POPs, and improvements in magnetic solid-phase extraction (MSPE) for POP analysis should be carried out with regard to the following four aspects: (1) development of novel applicable functionalized MNP adsorbents; (2) choice of suitable detection techniques; (3) combination of other extraction techniques; and (4) automation of MSPE. Graphical Abstract: